Exploring Indonesia’s Cultural Diversity through A Quick Response Code Quartet Card Game - Lukman Lukman; Yuniarti Yuniarti; Wawan Krismanto (APPLICATION: Applied science in Learning Research, 2025)
Teaching cultural diversity to students in the modern era requires integration with technology to make it engaging and challenging. For this reason, the study aims to develop learning media in the form of Quartet Cards with QR Code to explore Indonesian cultural diversity for grade 4 elementary school (SD) students. This research and development study uses the ADDIE model. The research background is social science learning for grade 4 in three schools (SD 12, 28, and 51) in Parepare, South Sulawesi, Indonesia. Data were collected through interviews, observations, needs analysis, validation, and practicality test questionnaires. Data analysis was carried out descriptive qualitatively, and quantitatively. The needs analysis showed that teachers and students needed game-based learning media that integrated technology to explore Indonesian cultural diversity. After design and development process, this study has produced a one set of Quartet Cards with QR Code. Based on the product validation test by material and media experts, the product was declared valid. The results of the practicality test by users (teachers and students) also showed that the product was very practical to use for learning. In conclusion, the product is valid & practical for elementary school students who want to explore Indonesian cultural diversity.